Предмет: Математика,
автор: andreyfrol199
-3 arcctg(корень -3) - 5 arctg(корень -3)=
Ответы
Автор ответа:
0
Наверное, не (корень -3), а -(корень 3).
Тогда:
-3·arcctg(-√3) - 5·arctg(-√3)= -3·150°-5·300°=450°+1500°=1950°=150°±n·360°=5π/6±n·2π
Тогда:
-3·arcctg(-√3) - 5·arctg(-√3)= -3·150°-5·300°=450°+1500°=1950°=150°±n·360°=5π/6±n·2π
Похожие вопросы
Предмет: Другие предметы,
автор: DragonLord132
Предмет: Українська мова,
автор: vikababunich
Предмет: Биология,
автор: iamzhenia1250
Предмет: Физика,
автор: Anton5679
Предмет: Алгебра,
автор: Lerka646